2019
DOI: 10.1051/bioconf/20191201021
|View full text |Cite
|
Sign up to set email alerts
|

Performance of resistant varieties (PIWI) at two different altitudes in Southern Brazil

Abstract: In southern Brazil there is a predominance of labrusca and hybrid varieties for wine and juice production due to climatic conditions of high rainfall, temperature and relative humidity. Growing varieties that combine disease resistance and wine quality (PIWI) can be an alternative to improve wine quality. The objective of this work was to evaluate the performance of three PIWI varieties (Felicia, Calardis Blanc and Aromera) in two regions (Videira, 27 • 01"S and 51 • 08"W, altitude 830 m; and São Joaquim, 28 •… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…When evaluating the same fungus resistant varieties in Videira (840m) in 2018 vintage, the same pattern of cycle duration was observed between the sub-periods evaluated (BRIGHENTI et al, 2019). Similar results were obtained for 'Felicia' and Calardis B. produced in São Joaquim (1100 m) (SOUZA et al, 2019).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…When evaluating the same fungus resistant varieties in Videira (840m) in 2018 vintage, the same pattern of cycle duration was observed between the sub-periods evaluated (BRIGHENTI et al, 2019). Similar results were obtained for 'Felicia' and Calardis B. produced in São Joaquim (1100 m) (SOUZA et al, 2019).…”
Section: Resultssupporting
confidence: 75%
“…Still in the 2018 vintage, but in a vineyard located at 1100 m, an average of 50 clusters were observed for 'Calardis Blanc' and 'Felicia'. In this experiment 'Felicia' also presented the heaviest clusters (on average 177 g) and was followed by 'Calardis Blanc' (134 g) (SOUZA et al, 2019). In a recent work that evaluated the adaptation of resistant varieties in northern Italy, it was found for 'Soreli' values of 3.5 kg per plant, 30 clusters per plant and an average of 120 g per cluster; for 'Sauvignon Kretos' it was found 2.4 kg per plant, 25 clusters per plant and an average of 107 g per cluster; and for 'Sauvignon Rytos' it was found 2.4 kg per plant, 29 clusters per plant and an average of 85 g per cluster (FRIONI et al, 2021).…”
Section: Resultsmentioning
confidence: 62%
“…These varieties have been adopted by numerous wine-growing countries, including renowned wine-producing nations such as France, Italy, Germany, and the United States. In addition, resistant grape varieties are increasingly being accepted in countries such as Brazil, Denmark, and Poland [5][6][7][8][9]. Despite their growing popularity, these grape varieties are still considered niche products in a niche market and have not yet made a breakthrough into the mainstream wine market [10,11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a previous study that evaluated the performance of PIWI varieties in Videira (840 m), it was observed that the average budbreak date of Calardis Blanc occurred on September 6, Bronner on September 11 and Felicia on August 29 (BRIGHENTI et al, 2019). In São Joaquim (1110 m) the average budbreak date of Calardis Blanc occurred on September 4, Aromera on September 12 and Felicia on August 30 (SOUZA et al, 2019). The budbreak date was similar to Merlot and Sangiovese (September 15) and similar to Sauvignon Blanc (September 22) (BRIGHENTI et al, 2013;BRIGHENTI et al, 2014).…”
Section: Resultsmentioning
confidence: 98%